Fibrosarcoma: Origin, differential diagnosis, and report of a case in the mandible - Harpreet Kaur; Vandana Gupta; Deepika Mishra; Vikender Singh Yadav (Wolters Kluwer Medknow Publications, 2022)
Fibrosarcoma (FS) is a malignant neoplasm of mesenchymal cells with no specific line of differentiation. Histologically, it mimics the wide spectrum of benign and malignant spindle cell neoplasms creating diagnostic conundrum. Immunohistochemistry plays a crucial role in the diagnosis which relies on various antibodies reacting with different antigens expressed by heterogeneous cells. Thus, there is a need to study the origin of the spindle cells to better comprehend their immunophenotypes that forms cornerstone for final confirmatory diagnosis. This case report describes the case of a 42-year-old male with soft-tissue mass in the mandible. Initial biopsy revealed it a reactive fibrous lesion; however, deeper biopsy confirmed spindle cell malignancy which exhibited immunonegativity to all other markers except vimentin. In addition, this case highlights the origin of various spindle cells with markers expressed during their development. The differential diagnosis of FS from other benign and malignant spindle cell lesions on the basis of clinical, histopathology, and immunohistochemistry is also elaborated.